Contemporary Problems in Early Childhood Education (Case Study at the President Filia Gracia Foundation Puruk Cahu Kindergarten) - Seprie Seprie (Syntax Idea)
The existence of government regulations regarding the one-village PAUD program indicates that education starting early is very important. Therefore, it is necessary to highlight several issues and problems in PAUD. This research aims to determine the issues and problems in contemporary PAUD. This research uses a qualitative research method, a literature study. The results of this research explain the meaning of contemporary PAUD issues and problems, issues in contemporary PAUD, the importance of PAUD, and behavioral problems in early childhood. This research concludes that contemporary PAUD issues are intended to discuss PAUD which is currently developing. Problems are problems that exist in the PAUD institution itself which lead to both positive and negative aspects, and basically with problems the science of PAUD will develop. With this problem, knowledge about PAUD will develop further. Therefore, responding to issues and problems in PAUD is very important, especially in the development of PAUD in formal education units such as the Kindergarten President of the Filia Gracia Puruk Cahu Foundation.